PENGARUH PMA, PMDN & INFLASI TERHADAP PDB SEKTOR INDUSTRI MANUFAKTUR DI INDONESIA : Dampak PMA, Investasi Dalam Negeri, dan Inflatie terhadap PDB Sektor Industri Manufaktur Indonesia - Silalahi, Bungaran; Linda Sari, Raina; SY, Muhammad (Universitas Jambi, 2025)
The manufacturing sector plays a strategic role in Indonesia’s economic structure. However, the growth of this sector is closely influenced by investment dynamics both Foreign Direct Investment (FDI) and Domestic Investment (DI) as well as inflation stability, which affects production efficiency and industrial competitiveness. This study aims to examine the effects of FDI in the manufacturing sector, DI in the manufacturing sector, and inflation on manufacturing sector Gross Domestic Product (GDP) in Indonesia over the period 2010–2024. Using a quantitative approach, this research applies multiple linear regression analysis to identify the relationship between investment variables, inflation, and manufacturing sector performance. The results show that, partially, FDI and DI have a positive effect on manufacturing GDP, while inflation has a negative effect. Simultaneously, the three variables significantly influence manufacturing GDP. These findings highlight that increasing investment, both foreign and domestic, is essential for strengthening production capacity and supporting the growth of the manufacturing industry. Meanwhile, maintaining stable and well-managed inflation is necessary to preserve efficiency and enhance the competitiveness of Indonesia’s manufacturing sector.